Restriction alleviation by bacteriophages lambda and lambda reverse. - Toothman, P (1981)
Deletion analysis indicated that the phage lambda restriction alleviation gene(s) ral resides between the cIII and N genes. The Ral+ phenotype was expressed only when lambda ral+ carried a modification such that it was resistant to restriction by the host specificity system. Under these conditions, Ral function protected superinfecting unmodified phages from restriction by EcoK or EcoB but not from restriction by EcoP1. Ral-protected phage DNA was not concomitantly K and B modified, but rather received only the modification specified by the system of the restricting host. Possible mechanisms for Ral action are discussed. Of the other lambdoid phages tested, the hybrid phage lambda rev had Ral activity, whereas phi 80vir and one lambda-P22 hybrid did not. The restriction alleviation activity of lambda rev called Lar, may be the same as the activity expressed in sbcA- strains of Escherichia coli, but it was functionally separable from exonuclease VIII activity (the product of the recE gene), which is also expressed in sbcA- strains.